Effect of disability level on response to pulmonary rehabilitation in patients with idiopathic pulmonary fibrosis - Kozu, R.; Jenkins, Susan; Senjyu, H. (2011)
Background and objective: It is unclear whether the severity of functional limitation resulting from IPF affects the response to pulmonary rehabilitation. The aim of this study was to compare the outcomes of rehabilitation in patients with IPF, who were grouped according to the Medical Research Council (MRC) dyspnoea scale. Methods: Sixty-five subjects (46, 71% men) with stable IPF were enrolled in an 8-week pulmonary rehabilitation programme. Subjects with MRC dyspnoea grades 2, 3 and 4 undertook a supervised outpatient programme, whereas subjects with MRC dyspnoea grade 5 participated in an unsupervised, home-based programme, with review every 2 weeks. The outcome measures included functional exercise capacity (6MWD), health status (Medical Outcomes Study Short Form 36 (SF-36)) and dyspnoea (transition dyspnoea index), which were measured at baseline and immediately after the programme. Hospitalizations for respiratory exacerbations were compared for the 12 months preceding and following the programme. Results: The number of subjects with MRC dyspnoea grades 2, 3, 4 and 5 were 16 (25%), 17 (26%), 17 (26%) and 15 (23%), respectively. There were differences between these groups in the magnitude of change in 6MWD, SF-36 and transition dyspnoea index (all P < 0.05). Specifically, subjects with MRC dyspnoea grade 2 or 3 demonstrated clinically and statistically significant improvements in 6MWD and SF-36 following rehabilitation (all P < 0.05). In contrast, for all measures, subjects with MRC dyspnoea grade 4 or 5 showed little or no improvement, or deteriorated following rehabilitation. Hospitalizations were reduced following rehabilitation only in subjects with MRC dyspnoea grade 2, 3 or 4 (P < 0.05). Conclusions: The response to pulmonary rehabilitation in subjects with IPF varies depending on the MRC grade of dyspnoea, with little benefit being observed in subjects with severe functional limitation. Responses to pulmonary rehabilitation were investigated in IPF patients, who were grouped according to the Medical Research Council (MRC) dyspnoea scale. Compared with those with severe disability (MRC dyspnoea grade 4 or 5), who received little or no benefit from rehabilitation, there were greater benefits for subjects with MRC dyspnoea grade 2 or 3. © 2011 Asian Pacific Society of Respirology.